Prevalence and natural history of variants in the ANKRD26 gene: a short review and update of reported cases. (17th November 2022) - Vyas, Hrushikesh; Alcheikh, Ahmad; Lowe, Gillian; Stevenson, William S; Morgan, Neil V; Rabbolini, David J
Abstract: ANKRD26 is a highly conserved gene located on chromosome 10p12.1 which has shown to play a role in normal megakaryocyte differentiation. ANKRD26 -related thrombocytopenia, or thrombocytopenia 2, is an inherited thrombocytopenia with mild bleeding diathesis resulting from point mutations the 5ʹUTR of the ANKRD26 gene. Point mutations in the 5ʹUTR region have been shown to prevent transcription factor-mediated downregulation of ANKRD26 in normal megakaryocyte differentiation. Patients with ANKRD26 -related thrombocytopenia have a predisposition to developing hematological malignancies, with acute myeloid leukemia and myelodysplastic syndrome most commonly described in the literature. We review the clinical features and biological mechanisms of ANKRD26 -related thrombocytopenia and summarize known cases in the literature.